Photonic multi-shape UWB pulse generation using a semiconductor optical amplifier-based nonlinear optical loop mirror - 罗博文 董建绩 于源 杨婷 张新亮 (Chinese physics B, 2013)
We propose and demonstrate a scheme to implement photonic multi-shape ultra-wideband（UWB） signal generation using a semiconductor optical amplifier（SOA） based nonlinear optical loop mirror（NOLM）.By employing the cross phase modulation（XPM） effect,cross gain modulation（XGM）,or both,multi-shape UWB waveforms are generated including monocycle,doublet,triplet,and quadruplet pulses.Both the shapes and polarities of the generated pulses are flexible to adjust,which may be very useful in UWB pulse shape modulation and pulse polarity modulation.